2019
DOI: 10.3390/ijerph16245001
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Vision Tests in Sports: Training Effects and Reliability of Peripheral Perception Test

Abstract: Various studies suggest the importance of peripheral vision (PV) in sports. Computer-based test systems provide objective methods to measure PV. Nevertheless, the reliability and training effects are not clarified in detail. The purpose of this investigation was to present a short narrative non-systematic review on computer-based PV tests and to determine the reliability and the training effects of peripheral perception sub-test (PP) of the Vienna test system (VTS) in a test–retest design. N = 21 male athletes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 45 publications
1
13
0
1
Order By: Relevance
“…Peripheral awareness was found to be superior in the present study's Premier League rugby players and is supported by the previous findings of Schumacher et al (2019) (21). However, Abernethy and Wood (2001), and Ryu et al (2013) found no differences in peripheral awareness when comparing expert and novices in racquet sports and soccer players, respectively (9,22).…”
Section: Speed Of Recognition Of Premier League Rugbysupporting
confidence: 89%
“…Peripheral awareness was found to be superior in the present study's Premier League rugby players and is supported by the previous findings of Schumacher et al (2019) (21). However, Abernethy and Wood (2001), and Ryu et al (2013) found no differences in peripheral awareness when comparing expert and novices in racquet sports and soccer players, respectively (9,22).…”
Section: Speed Of Recognition Of Premier League Rugbysupporting
confidence: 89%
“…A strong link between participation in fast-paced sports, requiring quick responses, and faster visuomotor processes is well documented [7,8,18]. However, there is less information about how these functions change with age and differ across sport discipline, gender, anthropometric variables, and sports experience (years of practice, training per week).…”
Section: Introductionmentioning
confidence: 99%
“…Secondary outcomes were FOV, VAL, VAR, and the TD. Detailed description and reliability are given elsewhere (Schumacher et al, 2019).…”
Section: Methodsmentioning
confidence: 99%